Sol-gel processing and phase characterization of Al2O3and Al2O3/SiC nanocomposite powders - Sukanda Jiansirisomboon (2018)
Monolithic Al2O3and Al2O3/SiC nanocomposite powders were prepared by sol-gel processing. The process involved the precipitation of Al(NO3)3·9H2O with NH4OH in excess water to form boehmite (AlOOH). XRD indicates that the subsequent thermal reaction proceeds by the phase transformation sequence AlOOH, γ-, δ-, θ-, to α-Al2O3. The27Al NMR spectra indicate a gradual increase in the proportion of Al in the tetrahedral sites of the γ-, δ- and θ-Al2O3formed at increasing calcination temperatures. Complete transformation to octahedral Al (α-Al2O3) is marked by the abrupt disappearance of tetrahedral Al. Al2O3/SiC nanocomposite powders were prepared by adding α-SiC powder to the boehmite precursor at the precipitation stage. Upon heating, the29Si NMR spectra of the Al2O3/SiC powders reveal α-SiC, Al2O3·xSiO2and SiO2phases. Stable α-Al2O3and α-Al2O3/SiC nanocomposite powders are formed at 1200 and 1300 °C, respectively. It appears likely that the presence of SiC modifies the thermal behaviour of the Al2O3in the nanocomposites by stabilising the Al2O3phases with concomitant oxidation of SiO2. © 2005 Elsevier Ltd. All rights reserved.